Numerical studies on electron beam quality optimization in a laser-driven plasma accelerator with external injection at SINBAD for ATHENAe. (November 2019) - Svystun, E N; Assmann, R W; Dorda, U; Marchetti, B; Martinez de la Ossa, A
Abstract: Nowadays the electron beams produced in plasma-based accelerators (PBAs) are of sufficient energy for multi-GeV applications. However, to allow PBAs to be usable for demanding applications such as Free-Electron Lasers, the quality and stability of plasma-accelerated beams have to be improved. We present numerical studies on acceleration of an RF-generated electron beam with a charge of 0.8 pC and initial mean energy of 100 MeV to GeV energies by a laser-plasma accelerator. This acceleration scheme is planned to be tested experimentally within the framework of the ATHENAe (Accelerator Technology HElmholtz iNfrAstructure) project at the SINBAD (Short INnovative Bunches and Accelerators at DESY) facility at DESY, Hamburg. Electron beam injection, acceleration and extraction from the plasma are investigated through start-to-end 3D simulations. The effect of the injection phase on the accelerated beam quality is investigated through tolerance studies on the arrival-time jitter between the electron beam and the external laser.